2021
DOI: 10.1002/cbic.202100449
|View full text |Cite
|
Sign up to set email alerts
|

Xanthopsin‐Like Systems via Site‐Specific Click‐Functionalization of a Retinoic Acid Binding Protein

Abstract: The use of light-responsive proteins to control both living or synthetic cells, is at the core of the expanding fields of optogenetics and synthetic biology. It is thus apparent that a richer reaction toolbox for the preparation of such systems is of fundamental importance. Here, we provide a proof-of-principle demonstration that Morita-Baylis-Hillman adducts can be employed to perform a facile site-specific, irreversible and diastereoselective click-functionalization of a lysine residue buried into a lipophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…1) [38][39][40] and of a p-hydroxycinnamate analogue of the photoactive yellow protein (PYP) chromophore structure. 41 The HBDI-LPs perform the E/Z photoisomerization with relatively high isomerization quantum yield in picosecond and subpicosecond timescale under UV/vis light irradiation. 38,39 These molecules share the common feature of an electronrich group conjugated to an electron-withdrawing group by means of an isomerizable carbon-carbon double bond, in order to generate push-pull cinnamic structures.…”
Section: Introductionmentioning
confidence: 99%
“…1) [38][39][40] and of a p-hydroxycinnamate analogue of the photoactive yellow protein (PYP) chromophore structure. 41 The HBDI-LPs perform the E/Z photoisomerization with relatively high isomerization quantum yield in picosecond and subpicosecond timescale under UV/vis light irradiation. 38,39 These molecules share the common feature of an electronrich group conjugated to an electron-withdrawing group by means of an isomerizable carbon-carbon double bond, in order to generate push-pull cinnamic structures.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our research team reported on the synthesis and characterization of molecular photoswitches inspired by the chromophore of GFP [38,39] . These photoswitches ( HDBI‐LPs in Figure 1, panel A) share with the natural GFP and PYP [67] chromophores, the cinnamic structure characterized by an aromatic ring connected by means of an exocyclic double bond to a carbonyl group. As introduced above, the cinnamic structure is also present in another chemical scaffold widely studied in our laboratories, namely ethyl 1‐methylene‐3‐phenyl‐1 H ‐indene‐2‐carboxylate, which we will call benzofulvene scaffold hereafter [68] .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our research team reported on the synthesis and characterization of molecular photoswitches inspired by the chromophore of GFP. [38,39] These photoswitches (HDBI-LPs in Figure 1, panel A) share with the natural GFP and PYP [67] chromophores, the cinnamic structure characterized by an…”
Section: Design and Synthesismentioning
confidence: 99%
“…The crystallographic structure of (E,E) diastereomer 2a was considered to constitute a good starting point for the structural characterization of 2b. Thus, the 1 H and 13 C NMR spectra of 2a were assigned and compared with those of the corresponding (E,Z) diastereomer 2b (Fig. 4 and 5).…”
Section: Synthesis and Structural Characterizationmentioning
confidence: 99%
“…1). [10][11][12][13][14] In the present work, the structure of our MBHA derivatives was manipulated in the aim of obtaining a tri(ethylene glycol)tethered MBHA dimer 1 (Fig. 2) potentially useful in the functionalization of materials containing reactive basic (i.e.…”
Section: Introductionmentioning
confidence: 99%